36 desain kitchen set pilihan / Fransisco Theo, Pungky Dwi Arfanto, Dionisius Inung ; penyunting Bima - FRANSISCO THEO; Pungky Dwi Arfanto; Dionisius Inung; Bima (Puspa Suara, 2014)
iv, 120 hlm : ilus ; 23 cm [3 eks]